Bovine leukosis virus detection in creole colombian breeds using nested-pcr (2011)
Using 360 DNA samples from eight Creole bovine breeds Blanco Orejinegro (BON), Casanareño (CAS), Costeño con Cuernos (CCC), Chino Santandereano (ChS), Caqueteño (CQT), Hartón del Valle (HV), Romosinuano (RS) and San Martinero (SM), two synthetic Colombian breeds: Lucerna (LUC) and Velásquez (VEL) and two introduced breeds Brahmán (B) and Holstein (H); the presence of Bovine Leukosis Virus (BLV) was evaluated through the amplification of a viral gene region env (provirus detection - nested-PCR). The percentage of presence and independence test were calculated (X²). Presence of BLV was higher in HV breed, followed by ChS (83.3% and 60% respectively); VEL and LUC breeds showed the same percentage (50%). In CAS, CCC and CQT the presence of virus was 26.7%, 23.3% y 16.7% respectively. On the other hand, no virus presence was found in BON, SM and RS. For the introduced breeds the presence of virus was 83.3% for H and 6.7% for B. The average of presence for Creole bovine breeds was lower than introduced breeds. A high and significant dependence was found between the presence of BLV with breed, sex and sampling places. The presence was lower in males than in females and in the northern than the southwestern and central areas of the country.